The Professional Organization of Science Teachers and Its Impact on Professionalism - Ayuvi, Ayda Al; Istanti, Fahrani Khoirunnisa; Salsabila, Amanda Nabila; Fadhilah, Nisrina Nuri; Mahardika, I Ketut (International Journal of Education, Information Technology, and Others, 2024)
Profession is work that is professional in nature. The teaching profession is a professional profession that requires preparation through special education and training. In essence, the profession is a statement or an open promise which states that a person is dedicating himself to a position. The teaching profession is a professional educator with the main task of educating, teaching, guiding, directing, training and assessing. Teachers have several special requirements, have a professional organization, have a code of ethics, and have the role of teacher rights and obligations which aim to guide students and evaluate good and specifically directed teaching and learning processes. The method in this article uses library research, namely a method of collecting data by understanding and studying theories from various literature related to the research, so that a work is obtained about Teacher Professional Organizations and their Impact on Professionalism.